2016
DOI: 10.1177/1559827616638288
|View full text |Cite
|
Sign up to set email alerts
|

Case Series in Lifestyle Medicine

Abstract: As the number of people living with chronic diseases climbs upward, novel methods to address the root causes of these disease are necessary to transform the state of our nation's health and our health care system. Interventions directed at making lasting lifestyle changes can have a major impact on the overall health of patients. In this pilot study, 4 obese patients, with unhealthy habits and abnormal blood profiles and biometrics, were able to significantly improve their lifestyles and their lab values with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…One solution could be to engage other team members beyond the physicians to play supportive roles. 44 We have found that various team members are already involved in supporting patient lifestyle interventions in family medicine practices. However, only 70% of physicians are practicing team-based care approaches.…”
Section: Discussionmentioning
confidence: 99%
“…One solution could be to engage other team members beyond the physicians to play supportive roles. 44 We have found that various team members are already involved in supporting patient lifestyle interventions in family medicine practices. However, only 70% of physicians are practicing team-based care approaches.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,14,24,49,50 Specific to this sample, our previous analysis of this same survey data indicates that 55% of LM practitioners reported frustration at not being able to receive reimbursement for utilizing LM in their practice, as well a lack of support for LM practice from colleagues and administrators. 51 The results of this analysis suggest that the team approach of LM, incorporating dietitians, coaches, exercise physiologists, health educators and others, 52-55 may address feelings of isolation within an ineffective system that respondents in this survey describe as rewarding volume over value. 12,46…”
Section: Discussionmentioning
confidence: 96%
“…40 Unlike acute conditions, chronic diseases require consistent care and management outside of the healthcare setting, in the community or primary care setting, in terms of medication, lifestyle management, and health behavior modification. [41][42][43][44][45] It is typically a multicomponent intervention that includes medication therapy review, patient medication education, medication monitoring, immunizations, disease self-care and support, and/or prescribing authority. Patients who take multiple medications due to chronic disease have a high risk of drug duplication, interaction, or adverse side effects, which could result in extended hospital stays and higher costs.…”
Section: Introductionmentioning
confidence: 99%